Efficacy and safety of rivaroxaban in preventing venous thromboembolism in postoperative patients with gynecological malignancies: protocol for a randomised controlled open-label trial (G-alfalfa trial) - Hong Zhou; Fei He; Ting Wei; Shuyi Wu; Jinhua Zhang; Huan Yi (BMJ Open)
Introduction Compared with the guideline-recommended use of low-molecular weight heparin (LMWH) for 28 days to prevent venous thromboembolism (VTE) after cytoreductive surgery, oral rivaroxaban avoids the pain and inconvenience of daily injections and reduces medical expenses. The proposed randomised controlled trial (RCT) aims to compare the efficacy and safety of rivaroxaban and enoxaparin in preventing VTE in patients after surgery for gynaecological malignancies and to provide a reference for clinical medication prevention.Methods and analysis This is a single-centre, randomised, controlled, open-label and assessor-blind clinical trial. Patients undergoing surgery for gynaecological malignancies will be randomly assigned in a 1:1 ratio to an oral rivaroxaban study group and a subcutaneous injection enoxaparin control group for anticoagulant prophylaxis. The medication administration begins 12–24 hours after surgery and continues for 28 days, with a 30-day follow-up after surgery. Clinical events during the treatment and the follow-up period will be observed. The primary endpoint will be any VTE. Secondary endpoints will be any bleeding event, medication compliance rate, rivaroxaban pharmacokinetics and pharmacogenomics. The sample size required for the G-alfalfa trial is derived based on power calculations of the VTE incidence in the two intervention regimens in previous literature.Ethics and dissemination This study was approved by the Ethics Committee of Fujian Maternal and Child Health Hospital on 2 April 2024 (Approval No.:2023KY174-03). The results of the trial will be submitted for publication in a peer-reviewed journal and presented at relevant conferences.Trial registration number Chinese Clinical Trial Registry (ChiCTR) 2300078535.